Exploring Outcomes of Service-Learning Participantion: Evidence from Pakistan - Hamdan Said; Iqbal Ahmad; Faizah Mohamad Nor (UUM Press, 2019)
Purpose - This study explored the perspectives of teachers on outcomes of service-learning participation in vocational training institutes. The main purpose was to gain a better understanding of outcomes concerning service-learning participation of vocational training institute students in Pakistan. Methodology - A total of 315 respondents participated in the study. Data were collected from 15 randomly selected vocational training institutes using a self-designed questionnaire which was drafted and validated after expert approval. The construct validation of the questionnaire was established through Exploratory Factor Analysis. Findings - The findings indicated that participation in service-learning resulted in increased course content knowledge, the development of interpersonal skills, and the development of a volunteering attitude among the vocational institute students. Significance - This study is one of the few studies related to academic outcomes of vocational education students as a result of service-learning participation. The results facilitate understanding of the pedagogical role of service-learning as a practical teaching approach, and would be of particular interest to employers who are looking for skilled manpower in the current job market.